CONFORTO TÉRMICO E COMPORTAMENTO DE NOVILHOS MACHOS NELORE EM SISTEMAS EM INTEGRAÇÃO LAVOURA–PECUÁRIA–FLORESTA - Flávio de Aguiar Coelho (2021)
The integrated Crop – Livestock – Forest systems are efficient in protecting the soil, promoting greater biodiversity to the system, and the arboreal component in reducing the incidence of direct solar radiation on production animals. Therefore, the aim of the study was: I - to evaluate the effect of different shade offers on the thermal distribution, ingestive and exploratory behavior of Nellore cattler, in the summer of the Cerrado biome. II – Apply automation techniques (infrared thermography, bioacoustics and global positioning management - GPS) in the prediction of microclimate, ingestive behavior and spatial exploration of grazing cattle. The trial was carried out in the summer of 2020, in the experimental area of the Brazilian Agricultural Research Corporation (EMBRAPA beef of cattle), located in the city of Campo Grande, Mato Grosso of Sul, Brazil. Twenty-four male Nellore cattler were randomly distributed in a randomized complete block design, in subdivided plots, with different shade offers: Two systems in Livestock – Forest integration, with different tree densities (ILF-22: 113 trees.ha-1; ILF -28: 89 trees.ha-1), and an unshaded pastoral system (NS). The total area of 18 ha was divided into 12 paddocks, with four replications per treatment. The tree component used was eucalyptus (Eucalyptus grandis x E. urophylla, clone H 13), distributed in simple rows spaced 22 and 28 meters between rows and 4 meters between trees. Microclimate, exploratory ingestive behavior were collected. Data were submitted to UNIVARIATE procedures to verify the normality of the data, to Pearson correlation and GLM for analysis of variance, with means compared by Tukey test at 5% significance. The forests of the systems in ILF-22 and ILF-28 presented better thermal distribution, with infrared temperature values lower than NS. There was an interaction of microclimate variables and comfort indices 24 hours a day (P<0.05). The projected shadow of the systems in integration provided lower values of radiant thermal load, black globe temperature, black globe temperature index and humidity and heat load index during the afternoon (P<0.05). The ILF-28 and NS systems showed better wind speed (P<0.05), with less heat accumulation in the ILF-28, with moderate scale negative correlation. There was an interaction of ingestive behavior in the hours (P<0.05). Grazing in the NS and ILF-22 systems was carried out with lower intensity during the night (P<0.05), and greater frequency and lower intensity of grazing, rumination and idleness in the ILF-28 system during the day and the night (P<0.05). The displacement of steers in the systems in ILF-22 and ILF-28 was higher (P<0.05), with exploration of the area visibly better in the system in ILF-28. However, the shade provided a better microclimate, with greater homogeneity in the orientation distribution in the behavior of cattler in the ILF-28 system. Also, infrared thermography, bioacoustics and global positioning management technologies were efficient methodological tools in describing the thermal distribution of the microclimate, the frequency and intensity of grazing, rumination and idle behavior in day and night periods, and spatial exploration of cattle to pasture.